Kepuasan dan Loyalitas Konsumen Minuman Kopi pada Aplikasi Grab di Kota Pangkalpinang - Saputra, Juan Arjuna; Karsiningsih, Eni; Muntoro, Muntoro (Universitas Galuh, 2024)
The tendency of urban people who have high mobility and limited time is one of the problems in society. Coffee shops are now present using food delivery services that are practical and easy to use to overcome these problems. The purpose of this study was to determine the factors that influence consumer satisfaction and loyalty to coffee drinks through the grab application in Pangkalpinang City. The research method used is a survey method with sampling techniques using purposive sampling, the number of samples studied was 100 respondents. The data analysis method uses Structural Equation Modeling (SEM) with the help of SmartPLS 4.0. The results of this study are e-trust has no effect on e-satisfaction, e-trust affects e-loyalty, e-service quality affects e-satisfaction, e-service quality has no effect on e-loyalty, e-satisfaction affects e-loyalty, e-trust has no effect on e-loyalty through e-satisfaction, e-service quality affects e-loyalty through e-satisfaction.